Students' Needs Analysis in an EFL Program for University Professors - Paula Andrea Bedoya; Luz María Valencia; Juan Carlos Montoya (Asociación Colombiana de Profesores de Ingles, 2015)
This study sets out to investigate professors' needs from an English as a foreign language program in a public university regarding demands, interests, and lacks based on the methodology of needs analysis. Data collected through a survey, focus groups, and individual interviews showed that professors need to meet the institutional language policy for contractual and academic reasons. Additionally, data revealed their desire to learn English to communicate in both academic and non-academic settings. Moreover, the lack of time and effective learning strategies were reported as comprising the main constraints for learning. Finally, the authors present the strengths and weaknesses of the program as well as the participants' suggestions for curriculum restructuring.